METHOD FOR INCREASING THE ACCURACY OF MEASUREMENT INTELLIGENT ELECTRICITY METERING SYSTEMS - R. K. Gereykhanov; A. M. Magomedov (Вестник Дагестанского государственного технического университета: Технические науки, 2016)
This article discusses the issues of improving the accuracy of measurements of the primary means of gathering information, the analysis of methods for automatic correction of errors on the basis of which the proposed solution to the problems associated with increasing the accuracy of data collection devices and electricity metering.